Cellular-free RAN slicing resource allocation algorithm based on multi-timescale collaboration - XIA Weiwei; WANG Boye; XIA Yaxing; MIAO Weiwei; WANG Dayang; JING Dongsheng; YAN Feng; SHEN Lianfeng (Tongxin xuebao)
To address the issue of ensuring user quality of service in resource allocation for 6G cell-free radio access network slicing under dynamic service variations, a resource allocation algorithm based on multi-timescale collaborative optimization was proposed. Firstly, the large time-scale slice-oriented resource allocation problem was formulated as a mean square error-minimization-based resource demand prediction model with average user latency constraints, and the accurate allocation of slice resources was achieved by a long and short-term memory time-series prediction network. Secondly, the small time-scale user-oriented resource allocation problem was formulated as a resource allocation model that maximized the system utility while guaranteeing the user transmission rate quality of service metric. Finally, a Proximal allocation algorithm based on Policy optimization multi-agent collaboration was introduced to enable dynamic resource allocation and real-time adjustment. Simulation results demonstrate that the proposed algorithm can accurately predict slice resource, improve the system transmission rates while reducing the average user latency and service blocking probability.